1985
DOI: 10.1063/1.865098
|View full text |Cite
|
Sign up to set email alerts
|

On the Smoluchowski paradox in a sedimenting suspension

Abstract: It is shown, by explicit calculation, that the influence of a plane wall supporting the Suspension on the Sedimentation velocity is such that the convergence problems of this quantity encountered in an unbounded Suspension do not occur-even in the limit of an infinitely distant wall. l. INTRODUCTIONThe motion of a particle in a viscous fluid causes a disturbance of the fluid flow which falls off very slowly with increasing distance to the particle, in fact only with the inverse first power of the distance. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The total 2 contribution to the sedimentation coefficient is evaluated here as 21.918Ϯ0.006. To relate this result to the previous papers, 32,46,48 we concentrate on comparison with Ref. 32, which contains the most complete calculation.…”
Section: Final Results and Conclusionmentioning
confidence: 79%
See 1 more Smart Citation
“…The total 2 contribution to the sedimentation coefficient is evaluated here as 21.918Ϯ0.006. To relate this result to the previous papers, 32,46,48 we concentrate on comparison with Ref. 32, which contains the most complete calculation.…”
Section: Final Results and Conclusionmentioning
confidence: 79%
“…Beenakker and Mazur evaluated b c in Ref. 46 ͑together with c ͒, however, the de-tails of the calculations have not been published. 47 Jones, Muthukumar, and Cohen 48 kept several terms in the scattering expansion of the three-particle hydrodynamic interactions, and get b c ϭ18.27.…”
Section: Introductionmentioning
confidence: 99%
“…Beenakker and Mazur30 calculated the mean velocity of a test sphere in a dilute suspension of identical spheres, settling toward an infinite horizontal flat plate and showed that only spheres in small interval of height affected that velocity. However, spheres in an interval close to the plate settled more slowly than those further away.…”
Section: Theorymentioning
confidence: 99%
“…We will assume that the spatial extension of the system is infinite so that we can ignore the boundary condition. The problem related to the non-applicability of the Navier-Stokes equation in an unbounded space will be also ignored [23,24]. Eqs.…”
Section: B Dynamicsmentioning
confidence: 99%